Karya Karawitan Eksperimental “Marebu Agung” - I Wayan Srutha Wiguna (GHURNITA: Jurnal Seni Karawitan, 2024)
"Marebu Agung" is an experimental music composition that inspired the idea of the Ngerebong ceremony in Kesiman Petilan Village, East Denpasar, Denpasar City. The composer's interest in the aspects of the Ngerebong ceremony, such as ritual aspects through the ceremony stages and musical elements through the instruments or gamelan that accompany the ceremony, drove the composer to realize it in an experimental artwork. In this case, the composer aimed to transform the Ngerebong ceremony into an experimental music composition by combining the musical aspects of the ceremony, including Ancag-ancagan or Leluangan motifs on the Gong Kebyar and motifs of Batel, Bapang, and kale on the Baleganjur Bebarongan. Marebu means neutralizing, while agung means nature, so marebu agung means neutralizing or purifying nature. In this case, it refers to the Ngerebong ceremony itself, carried out to purify the nature of Kesiman. Three problem formulations become the focus of this creation: how the creation process, form, and aesthetics. Methods used in the creation process is Panca Stithi Ngawi Sani from I Wayan Dibia, consisting of ngawirasa, ngewacak, ngerencana, ngawangun, and ngebah. This creation's theories include creativity, aesthetics, and transformation. This creation has a magical tone and highlights pattern processing based on combining two Karawitan motifs in the Ngerebong ceremony.